Automatic indexed calculation of wachspress' rational finite element functions - Dalton, G.R. (Computers & mathematics with applications (1987), 1985)
A numerical method of calculating all of the polynomial coefficients for Wachspress' rational finite element functions is presented. It requires only linear algebraic computations of matrix algebra and avoids the complicated constructions of geometric algebra used in the development of the rational elements.